An innovative leadership development initiative to support building everyday resilience in health systems. Issue 7 (18th May 2021) - Nzinga, Jacinta; Boga, Mwanamvua; Kagwanja, Nancy; Waithaka, Dennis; Barasa, Edwine; Tsofa, Benjamin; Gilson, Lucy; Molyneux, Sassy
Abstract: Effective management and leadership are essential for everyday health system resilience, but actors charged with these roles are often underprepared and undersupported to perform them. Particular challenges have been observed in interpersonal and relational aspects of health managers' work, including communication skills, emotional competence and supportive oversight. Within the Resilient and Responsive Health Systems (RESYST) consortium in Kenya, we worked with two county health and hospital management teams to adapt a package of leadership development interventions aimed at building these skills. This article provides insights into: (1) the content and co-development of a participatory intervention combining two core elements: a complex health system taught course, and an adapted communications and emotional competence process training; and (2) the findings from a formative evaluation of this intervention which included observations of the training, individual interviews with participating managers and discussions in regular meetings with managers. Following the training, managers reported greater recognition of the importance of health system software (values, belief systems and relationships), and improved self-awareness and team communication. Managers appeared to build valued skills in active listening, giving constructive feedback, 'stepping back' from automatic reactions to challenging emotional situations and taking responsibility to communicate with emotional competence. The training also created spaces for managers to share experiences, reflect upon and nurture social competences. We draw on our findings and the literature to propose a theory of change regarding the potential of our leadership development intervention to nurture everyday health system resilience through strengthening cognitive, behavioural and contextual capacities. We recommend further development and evaluation of novel approaches such as those shared in this article to support leadership development and management in complex, hierarchical systems.